One-step route to tricyclic fused 1,2,3,4-tetrahydroisoquinoline systems via the Castagnoli–Cushman protocol - Pashev, Aleksandar; Burdzhiev, Nikola; Stanoeva, Elena (Beilstein Journal of Organic Chemistry, 2020)
The Castagnoli–Cushman reaction of 3,4-dihydroisoquinolines with glutaric anhydride, its oxygen and sulfur analogues was investigated as a one-step approach to the benzo[a]quinolizidine system and its heterocyclic analogs. An extension towards the pyrrolo[2,1-a]isoquinoline system was achieved with the use of succinic anhydride. The results are evidence of an unexplored method for the access of the aforementioned tricyclic annelated systems incorporating a bridgehead nitrogen atom. The structures and relative configurations of the new compounds were established by means of 1D and 2D NMR techniques. The reactions between 1-methyldihydroisoquinoline and glutaric, diglycolic and succinic anhydrides yielded unexpected isoquinoline derivatives containing an exocyclic double bond. The compounds prepared bear the potential to become building blocks for future synthetic bioactive molecules.
Keywords: benzo[a]quinolizidinones; Castagnoli–Cushman reaction; 3,4-dihydroisoquinolines; monocyclic anhydrides; pyrrolo[2,1-a]isoquinolinones

Heterocycles in Natural Product Synthesis - Garrido Montalban, A. (Quinolines and Isoquinolines, 2011)

(untitled) - Dwek, R. A.; Butters, T. D.; Platt, F. M.; Zitzmann, N. (Nat. Rev. Drug Discovery, 2002)

(untitled) - Boehringer, M.; Fischer, H.; Hennig, M.; Hunziker, D.; Huwyler, J.; Kuhn, B.; Loeffler, B. M.; Luebbers, T.; Mattei, P.; Narquizian, R.; Sebokova, E.; Sprecher, U.; et al. (Bioorg. Med. Chem. Lett., 2010)

(untitled) - Mattei, P.; Boehringer, M.; Di Giorgio, P.; Fischer, H.; Hennig, M.; Huwyler, J.; Koçer, B.; Kuhn, B.; Loeffler, B. M.; MacDonald, A.; Narquizian, R.; Rauber, E.; et al. (Bioorg. Med. Chem. Lett., 2010)

(untitled) - Zaarur, N.; Gabai, V. L.; Porco, J. A., Jr; Calderwood, S.; Sherman, M. Y. (Cancer Res., 2006)

(untitled) - Pashev, A. S.; Burdzhiev, N. T.; Stanoeva, E. R. (Org. Prep. Proced. Int., 2016)

(untitled) - Matveeva, M. D.; Purgatorio, R.; Voskressensky, L. G.; Altomare, C. D. (Future Med. Chem., 2019)

Alkaloids: Chemistry and Biology - Pässler, U.; Knölker, H.-J. (The Pyrrolo[2,1-a]isoquinoline Alkaloids, 2011)

(untitled) - Castagnoli, N. (J. Org. Chem., 1969)

(untitled) - Cushman, M.; Castagnoli, N. (J. Org. Chem., 1973)

U.S. Patent - Shetty, B. V.; McFadden, A.; Hofer, P. (Analgesic 4-carboxy-pyrrolidin-2-one compound, 1984)

(untitled) - Dar’in, D.; Bakulina, O.; Chizhova, M.; Krasavin, M. (Org. Lett., 2015)

(untitled) - Haimova, M. A.; Mollov, N. M.; Ivanova, S. C.; Dimitrova, A. I.; Ognyanov, V. I. (Tetrahedron, 1977)

(untitled) - Cushman, M.; Gentry, J.; Dekow, F. W. (J. Org. Chem., 1977)

(untitled) - Shaw, J. T. (Nat. Prod. Rep., 2009)

(untitled) - Ng, P. Y.; Masse, C. E.; Shaw, J. T. (Org. Lett., 2006)

(untitled) - Di Maso, M. J.; Snyder, K. M.; De Souza Fernandes, F.; Pattawong, O.; Tan, D. Q.; Fettinger, J. C.; Cheong, P. H.-Y.; Shaw, J. T. (Chem. – Eur. J., 2016)

(untitled) - Tan, D. Q.; Younai, A.; Pattawong, O.; Fettinger, J. C.; Cheong, P. H.-Y.; Shaw, J. T. (Org. Lett., 2013)

(untitled) - Pattawong, O.; Tan, D. Q.; Fettinger, J. C.; Shaw, J. T.; Cheong, P. H.-Y. (Org. Lett., 2013)

(untitled) - Georgieva, A.; Stanoeva, E.; Spassov, S.; Macicek, J.; Angelova, O.; Haimova, M.; De Kimpe, N. (Tetrahedron, 1991)

(untitled) - Stanoeva, E.; Georgieva, A.; Avramova, S.; Burdzhiev, N.; Lázár, L. (J. Heterocycl. Chem., 2015)

(untitled) - Cushman, M.; Madaj, E. J. (J. Org. Chem., 1987)

(untitled) - Tang, Y.; Fettinger, J. C.; Shaw, J. T. (Org. Lett., 2009)

(untitled) - Bakulina, O.; Ivanov, A.; Suslonov, V.; Dar’in, D.; Krasavin, M. (Beilstein J. Org. Chem., 2017)

(untitled) - González-López, M.; Shaw, J. T. (Chem. Rev., 2009)

(untitled) - Chizhova, M.; Dar'in, D.; Krasavin, M. (Tetrahedron Lett., 2017)

(untitled) - Stanoeva, E.; Haimova, M.; Ognyanov, V. (Liebigs Ann. Chem., 1984)

(untitled) - Kametani, T.; Terasawa, H.; Ihara, M. (J. Chem. Soc., Perkin Trans. 1, 1976)

(untitled) - Krasavin, M.; Dar’in, D. (Tetrahedron Lett., 2016)

(untitled) - Valenta, V.; Holubek, J.; Svátek, E.; Dlabač, A.; Bartošová, M.; Protiva, M. (Collect. Czech. Chem. Commun., 1983)

(untitled) - Brossi, A.; Dolan, L. A.; Teitel, S. (Org. Synth., 1977)

(untitled) - Burdzhiev, N. T.; Stanoeva, E. R. (Tetrahedron, 2006)

(untitled) - Burdzhiev, N.; Stanoeva, E.; Shivachev, B.; Nikolova, R. (C. R. Chim., 2014)

(untitled) - Burdzhiev, N. T.; Stanoeva, E. R. (Z. Naturforsch., B: J. Chem. Sci., 2008)

(untitled) - Dubs, C.; Hamashima, Y.; Sasamoto, N.; Seidel, T. M.; Suzuki, S.; Hashizume, D.; Sodeoka, M. (J. Org. Chem., 2008)

(untitled) - Kóbor, J.; Sohár, P.; Fülöp, F. (Tetrahedron, 1994)

(untitled) - Lenz, G. R. (J. Org. Chem., 1976)

(untitled) - Kametani, T.; Takahashi, T.; Honda, T.; Ogasawara, K.; Fukumoto, K. (J. Org. Chem., 1974)

(untitled) - Yu, C. K.; MacLean, D. B.; Rodrigo, R. G. A.; Manske, R. H. F. (Can. J. Chem., 1970)

(untitled) - Amat, M.; Santos, M. M. M.; Bassas, O.; Llor, N.; Escolano, C.; Gómez-Esqué, A.; Molins, E.; Allin, S. M.; McKee, V.; Bosch, J. (J. Org. Chem., 2007)

Comprehensive Heterocyclic Chemistry III - Avendaño, C.; Menéndez, J. C. (Bicyclic 6-6 Systems with One Bridgehead (Ring Junction) Nitrogen Atom: No Extra Heteroatom, 2008)

(untitled) - Sugiura, M.; Takao, N.; Iwasa, K.; Sasaki, Y. (Chem. Pharm. Bull., 1978)

(untitled) - Fülöp, F.; Bernäth, G.; El-Gharib, M. S.; Kóbor, J.; Sohár, P.; Pelczer, I.; Argay, G.; Kálmán, A. (Chem. Ber., 1990)

(untitled) - Zalán, Z.; Hetényi, A.; Lázár, L.; Fülöp, F. (Tetrahedron, 2005)

(untitled) - Van der Eycken, E.; Deroover, G.; Toppet, S. M.; Hoornaert, G. J. (Tetrahedron Lett., 1999)

(untitled) - Strandtmann, M. v.; Cohen, M. P.; Shavel, J., Jr (J. Org. Chem., 1966)

(untitled) - Sosnovskikh, V. Y.; Usachev, B. I.; Sizov, A. Y.; Vorontsov, I. I.; Shklyaev, Y. V. (Org. Lett., 2003)

(untitled) - Tyutin, V. Y.; Chkanikov, N. D.; Shklyaev, V. S.; Shklyaev, Y. V.; Kolomiets, A. F.; Fokin, A. V. (Bull. Acad. Sci. USSR, Div. Chem. Sci. (Engl. Transl.), 1992)

(untitled) - Sviridov, V. D.; Chkanikov, N. D.; Shklyaev, Y. V.; Kolomiets, A. F.; Fokin, A. V. (Chem. Heterocycl. Compd., 1990)

(untitled) - Sviridov, V. D.; Chkanikov, N. D.; Galakhov, M. V.; Shklyaev, Y. V.; Shklyaev, V. S.; Aleksandrov, B. B.; Gavrilov, M. S. (Bull. Acad. Sci. USSR, Div. Chem. Sci. (Engl. Transl.), 1990)

(untitled) - Baldwin, J. E. (J. Chem. Soc., Chem. Commun., 1976)

(untitled) - Fulmer, G. R.; Miller, A. J. M.; Sherden, N. H.; Gottlieb, H. E.; Nudelman, A.; Stoltz, B. M.; Bercaw, J. E.; Goldberg, K. I. (Organometallics, 2010)

(untitled) - Sheldrick, G. M. (Acta Crystallogr., Sect. C: Struct. Chem., 2015)

(untitled) - Dolomanov, O. V.; Bourhis, L. J.; Gildea, R. J.; Howard, J. A. K.; Puschmann, H. (J. Appl. Crystallogr., 2009)